PENERAPAN METODE PROJECT ORIENTED PROBLEM BASED LEARNING (POPBL) UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS X MIPA 5 DI MAN 1 KOTA MALANG - Lika Anis Zahro; Chalimatus Sadiyah; Abdul Jalil (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This classroom action research aims to describe the application and improvement of student learning outcomes by using the Project Oriented Problem Based Learning (POPBL) learning method on Sejarah Kebudayaan Islam subjects in class X MIPA 5 in MAN 1 Kota Malang. The problem faced is that there are still many students whose learning outcomes are low because the teacher still uses the old method during the learning process. Data sources used by researchers are primary data sources in the form of observation, test and documentation. Also secondary data sources in the form of documents or notes and documentation photos during teaching activities in the classroom. The result of this study indicate an increase in student learning outcomes, namely in the pre-cycle, the percentage of learning completeness by 15%, then at the first cycle of 43%, and when the improvement in the second cycle, the percentage of student learning completeness increased by 100%. Keywords: Project Oriented Problem Based Learning (POPBL), Islamic Cultural History, Learning Outcomes